Fabrication and evaluation of adhesion enhanced flexible carbon nanotube transparent conducting films1. Issue 15 (21st April 2015) - Wang, Yan; Yang, Hai-Jie; Geng, Hong-Zhang; Zhang, Ze-Chen; Ding, Er-Xiong; Meng, Yan; Luo, Zhi-Jia; Wang, Jing; Su, Xiao-Mei; Da, Shi-Xun
<x xml:space="preserve">Abstract</x> The addition of polyacrylic acid to SWCNT dispersion improved the film adhesion obviously without decreasing its electrical conductivity.